1985
DOI: 10.1007/bf01908189
|View full text |Cite
|
Sign up to set email alerts
|

Effect of adenosine and AICAR on ATP content and regional contractile function in reperfused canine myocardium

Abstract: We investigated whether the postischemic acceleration of adenosine triphosphate (ATP) synthesis by means of precursor infusion is beneficial for the contractile function of reperfused myocardium. A coronary artery was occluded for 45 min in 21 dogs to produce a marked but reversible ischemia. During the following 3 hours of reperfusion either adenosine (n = 6) or AICAR (5-amino-imidazole-4-carboxamide-riboside) (n = 6) was infused intracoronarily by a small transfemoral catheter positioned in the LAD. ATP repl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

1986
1986
2001
2001

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(21 citation statements)
references
References 44 publications
(51 reference statements)
1
19
0
1
Order By: Relevance
“…This metabolic difference between adenosine-pretreated and control hearts did not appear to influence functional recovery ( Figure 5). This agrees with the observations of other investigators (17,29), who also were unable to demonstrate an influence of cardiac ATP on functional recovery from ischaemia. In spite of this, ATP has beenwidely and successfully used as an indicator of the extent of ischaemic changes in the heart.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This metabolic difference between adenosine-pretreated and control hearts did not appear to influence functional recovery ( Figure 5). This agrees with the observations of other investigators (17,29), who also were unable to demonstrate an influence of cardiac ATP on functional recovery from ischaemia. In spite of this, ATP has beenwidely and successfully used as an indicator of the extent of ischaemic changes in the heart.…”
Section: Discussionsupporting
confidence: 93%
“…Even in the presence of adenosine no increase of ATP during recovery was observed, which is in contrast to an enhanced adenosine uptake and increase of ATP in the reperfused, regionally ischaemic dog heart (28). In the rat, there seems to be a failure of the energy producing or distributing processes rather than a failure of energy utilisation (17) reported in dogs.…”
Section: Discussionmentioning
confidence: 95%
“…Glower et al reported 24 hours of recovery following 15 minutes of ischemia in the conscious dog (9). Kloner et al (18) found long lasting dysfunction after a short period of regional ischemia, and Vial et al (36) as well as a recent paper from our laboratory showed a regional dysfunction for several hours in open-chest dog preparations (13). It was demonstrated by Heyndrickx et al (12) that 5 minutes of ischemia are long enough to produce a prolonged postischemic dysfunction.…”
Section: Regional Functionmentioning
confidence: 89%
“…Regional sonomierometry was performed according to Hagl (10) as previously described (13). Two pairs of small ultrasound transducers (1.5 mm diameter approximately) were implanted in a subendocardial position oriented to the minor axis of the left ventricle (about 13 mm distance each pair).…”
Section: Methodsmentioning
confidence: 99%
“…On this subject, Hoffmeister et al reported that an experimental promotion of recovery of ATP content in the myocardium did not produce any improvement in contractility. 13 It seems that there may be a greater delay in the recovery of contraction compared with ATP content, even though CV-11974 improves myocardial energy metabolism during reperfusion.…”
Section: Discussionmentioning
confidence: 99%